2009
DOI: 10.1103/physrevb.79.075322
|View full text |Cite
|
Sign up to set email alerts
|

Spin and phase coherence measured by antilocalization inn-InSbthin films

Abstract: The spin and phase coherence times of the itinerant electrons in n-InSb thin films were experimentally determined by analyzing the low-temperature magnetoresistance in antilocalization theory. The results indicate a very weak temperature dependence below 10 K for the spin coherence time. The dependence of the spin coherence time on carrier density demonstrates that the Elliott-Yafet mechanism is predominantly responsible for electron-spin relaxation in n-type InSb at low temperatures. The phase coherence time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
5
21
0
Order By: Relevance
“…The increase by adatom coverage has been observed in metals systems 7 and has been proposed as a means of increasing the average SOI in low-SOI systems like graphene 21 . Figure 6 indicates that for both bare and covered mesas τ −1 SO is not strongly T -dependent within the experiment range of T , consistent with previous discussions 22 . The residual T -dependence, and the small differences in relative magnitudes of the increase in τ −1 SO dependent on RE ion, are the result of several competing effects and must be relegated to future study.…”
supporting
confidence: 90%
“…The increase by adatom coverage has been observed in metals systems 7 and has been proposed as a means of increasing the average SOI in low-SOI systems like graphene 21 . Figure 6 indicates that for both bare and covered mesas τ −1 SO is not strongly T -dependent within the experiment range of T , consistent with previous discussions 22 . The residual T -dependence, and the small differences in relative magnitudes of the increase in τ −1 SO dependent on RE ion, are the result of several competing effects and must be relegated to future study.…”
supporting
confidence: 90%
“…For longitudinal-optical-phonon scattering, as τ −1 p varies slower than 1/ ε 3 k ∼ T −3 , τ s still decreases with temperature. It was observed that at high density in the degenerate regime the spin lifetime varies slowly with temperature [544,555,560]. This is understood as that in degenerate regime the ionizedimpurity scattering and longitudinal-optical-phonon scattering times, as well as ε k , vary slowly with temperature [see Eq.…”
Section: Electron Spin Relaxation In N-type Bulk Iii-v and Ii-vi Semimentioning
confidence: 96%
“…Fortunately, advances in the development of the growth of InSb heterostructures, 4 low temperature electron mobilities of > 100,000 cm 2 V −1 s −1 are now achievable in InAlSb/InSb QWs 5-7 and ballistic transport is evident in devices with greater than µm dimensions, producing spin coherence lengths of 2 µm. 8 There have been a number of experimental reports of spin detection using ballistic transport 9 and even more have been proposed 10,11 . Spin dependent transverse focusing is one such route and has been observed in pGaAs 12 and n-InSb 13,14 QWs.…”
Section: Introductionmentioning
confidence: 99%